Plexiform Melanocytic Schwannoma: Report of a Second Case and Overview of a Rare Entity. (2nd December 2022) - Ranson, Marc; Lai, Jonathan; Van Brenk, Bert; McCalmont, Timothy H.; Walsh, Noreen M.
Abstract: The seminal case report of plexiform melanocytic schwannoma, published a decade ago, indicated that this is a rare variant of schwannoma demonstrating immunohistochemical expression of melanocytic markers, electron microscopic evidence of melanosome formation, and genetic features of a benign schwannoma. We report herein, a second example of this entity. Of added interest, our case showed pseudoglandular features, as previously recorded in other variants of schwannoma. A 66-year-old man presented with a cutaneous papule on the abdomen. Histopathologically, a vertically oriented, exoendophytic, folliculocentric, dermal tumor with a plexiform architecture was observed. This was composed of nodules and diverging fascicles of bland spindle-shaped cells. Notable interstitial mucin deposition conveyed a pseudoglandular appearance to the lesion. The spindled cells co-expressed S100, SOX10, and HMB45. A minority of cells expressed Melan-A and MiTF. EMA and claudin-1 stained capsular and perifascicular perineurial cells. Melanin was absent. Plexiform melanocytic schwannoma represents one of several nerve sheath tumors that peculiarly display evidence of melanocytic differentiation. These include melanocytoneuroma, pigmented neurofibroma (or melanocytic neurofibroma), and malignant melanotic schwannian tumor. Of importance, these proliferations can be mistaken for melanocytic tumors, including melanoma. In expanding the literature on this topic, we discuss steps required to distinguish plexiform melanocytic schwannoma from melanoma and other nerve sheath tumors with melanocytic differentiation. The possible pathogenesis of these unusual neoplasms is also addressed.